PP.39.20: ACE-INDEPENDENT RAS ENZYME ACTIVITIES IN HEART TRANSPLANT PATIENTS WITH CHRONIC KIDNEY DISEASE. (June 2015) - Kovarik, J.J.; Kopecky, C.; Antlanger, M.; Domenig, O.; Kaltenecker, C.C.; Werzowa, J.; Hecking, M.; Mahr, S.; Kain, R.; Zuckermann, A.; Poglitsch, M.; Säemann, M.D.
Abstract : Objective: Angiotensin-converting enzyme inhibitors (ACEis) are beneficial in patients with heart failure and chronic kidney disease (CKD), yet their direct effects on the heart tissue remain inconclusive. It has been suggested that ACEi do not lead to continuous suppression of systemic angiotensin Ang II levels, but may exert beneficial effects by upregulating Ang 1–7, the suggested antagonist of Ang II. Here we determined the specific contributions of ACE and ACE-independent enzymes to systemic and local Ang-II and Ang 1–7 formation in heart-transplanted (HTX) patients with CKD under ACEi therapy. Design and method: In this cross-sectional, exploratory study we investigated local and systemic angiotensin formation in HTX patients. Right ventricular biopsies of allograft recipients (n = 12, with ACEi treatment and no RAS blockade) were used for assessing cardiac RAS activity by a highly sensitive mass spectrometry based assay. Ang I was spiked to biopsy homogenates, incubated in the presence or absence of selective enzyme inhibitors and the ACE and chymase mediated Ang II formation was measured. Accordingly, we assessed RAS enzyme mediated Ang 1–7 formation from Ang I as well as 1–7 formation from Ang II. Results: We demonstrated that the Ang II formation in plasma is completely ACE depended while ACEis are not efficient to inhibit cardiac Ang II formation in HTX patients. Conversely, cardiac Ang II formation was predominantly chymase-dependent. ACEi therapy significantly upregulated Ang I and Ang 1–7 plasma levels, but did not affect cardiac Ang 1–7 formation rates. The enzymes neprilysin and prolylendopeptidase significantly contributed to cardiac Ang 1–7 formation directly from Ang I and surprisingly, prolylcarboxypeptidase dominated Ang 1–7 formation from Ang II compared to a minor contribution of ACE2 in myocardial tissue of HTX patients independent of ACEi therapy. Conclusions: The local and systemic RAS is differentially regulated in HTX patients. While plasma Ang II formation is ACE-dependent, the cardiac formation of Ang II is chymase-depended. Neprilysin, prolylendopeptidase and prolylcarboxypeptidase are the major contributors of cardiac Ang 1–7 formation independent of ACE2 activity and ACEi therapy. These findings provide molecular background for ACEi therapy with considerable impact on novel RAS-interfering therapeutic approaches.